PENINGKATAN PERAN KOLABORASI PENTAHELIX DALAM UPAYA KESIAPSIAGAAN MENGENAI BENCANA MULTIHAZARD DI KABUPATEN BANYUWANGI - Setya Haksama; Diansanto Prayoga; M. Farid Dimjati Lusno; Jayanti Dian Eka Sari; Syifaul Lailiyah; Muhammad Harisul Ilmi; Jessika Pramudya Wardani; Oktario Dinansa Khoir; Mabub Junaidi; Syadza Zahrah Shedyta; Syahprevi Rayyan Zeinsar; M. Rifqo H. Farid; Abdul Fattah Farid (STKIP PGRI SITUBONDO, 2022)
Natural disasters are disasters caused by natural events, such as earthquakes, tsunamis, volcanic eruptions, floods, droughts, hurricanes, and landslides. Geologically, Indonesia is included as a country that is prone to natural disasters. Banyuwangi Regency is one of the areas in Indonesia with a high threat of multi-hazard disasters. One way that can be done to maximize preparedness efforts is by collaboration between all related sectors, one of which can be implemented is the Pentahelix disaster collaboration. For this reason, a Community Service Program was held in Banyuwangi Regency to provide education and training on Pentahelix collaboration. As well as a deep understanding of each sector's role in the disaster. From this community service, the results were obtained in the form of improvement and an in-depth understanding of each sector's role in the disaster.